The Effect of Stress Due to Fatigue, Flight Duration, and Situation Awareness on Pilot Flight Performance - Aziz, Achmad Maulana Rafi’uzzaky; Kalbuana, Nawang; Prasetya, Catur Sidiq (Universitas Muhammadiyah Gresik, 2025)
This study aims to examine several factors that influence stress caused by fatigue, flight duration, and situational awareness that affect pilot flight performance. This study uses a literature research method by collecting and analyzing literature found in various journals, scientific articles, and related literature sources. This study will identify that fatigue, situational awareness, and long flight duration are factors that cause increased stress levels, which significantly disrupt cognitive abilities, decision making, and concentration in pilots during flights. When pilots have a high level of situational awareness, it can have an impact as a mitigation factor that can reduce the negative impact of stress on pilot flight performance. The findings of this research and literature review are expected to provide a basis for developing strategies for stress management and for improving situational awareness that has an impact on flight safety and security because it affects pilot performance for decision making in emergency situations. Keywords: Flight performance, fatigue, flight duration, and situational awareness